2017
DOI: 10.1111/jcmm.13397
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tenascin X gene function impairs injury‐induced stromal angiogenesis in mouse corneas

Abstract: To determine the contribution by tenascin X (Tnx) gene expression to corneal stromal angiogenesis, the effects were determined of its loss on this response in TNX knockout (KO) mice. In parallel, the effects of such a loss were evaluated on vascular endothelial growth factor (VEGF) and transforming growth factor b1 (TGFb1) gene and protein expression in fibroblasts and macrophages in cell culture. Histological, immunohistochemical and quantitative RT-PCR changes determined if Tnx gene ablation on angiogenic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Immunostaining detected TNX expression in the peripheral stroma, but not in the central, cornea of an uninjured animal as previously reported (data not shown) [ 36 ]. However, during the epithelial healing process TNX protein expression was evident up to 36 h (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Immunostaining detected TNX expression in the peripheral stroma, but not in the central, cornea of an uninjured animal as previously reported (data not shown) [ 36 ]. However, during the epithelial healing process TNX protein expression was evident up to 36 h (Fig.…”
Section: Resultssupporting
confidence: 84%
“…TNXB contributes to angiogenesis and the decrease of TGFb1 expression level in TNXB knockout mice was reported as modulated by VEGF-A. TNXB acts by encouraging neovascularization and by suppressing anti-angiogenic VEGF-B mRNA expression in vivo (Sumioka et al, 2018). Moreover, it is mutated in a small cohort of patients affected by Ehlers-Danlos syndromes, a heterogeneous group of rare monogenic conditions characterized by vascular and generalized connective tissue fragility (Malfait, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies in Tnxb –/– mice revealed the presence of reduced femoral bone mass with enhanced osteoclast differentiation and bone-resorbing ability ( Kajitani et al, 2019 ), very mild genito-urinary complications (rectal prolapse in <1%) in female mice compared to uterine and vaginal prolapse seen in clEDS patients ( Egging et al, 2008 ), attenuated stromal neovascularization following cauterization ( Sumioka et al, 2018 ) and gastric dysfunction associated with abnormal gastric sensory function ( Aktar et al, 2019 ). Additionally, Tnxb –/– mice showed increased anxiety-like behavior as well as superior sensorimotor coordination and emotional learning and memory, without differences in locomotor or home cage activity ( Kawakami and Matsumoto, 2011 ; Voermans et al, 2011 ).…”
Section: Animal Models Mimicking Ehlers–danlos Syndromesmentioning
confidence: 99%